Comprehensive database on Induan (Lower Triassic) to Sinemurian (Lower Jurassic) marine bivalve genera and their paleobiogeographic record - Ros Franch, Sonia (2014)
Marine bivalve genera that were described or mentioned for Triassic and Lower Jurassic deposits worldwide are reviewed in terms of their validity, stratigraphic range, paleogeographic distribution, paleoautoecology and shell mineralogy. Data were originally compiled at species level and are arranged systematically. A brief discussion for each genus includes synonymy, taxonomic status and included subgenera, as well as current uncertainties about their validity and range. The distribution of each genus is also shown on paleogeographic maps. Type species and first and last appearances of each genus are also mentioned. We recognize as valid 280 genera and their included subgenera, and we further discurss 148 genera (arranged alphabetically) which were mentioned for the study interval but are not included for different reasons. The purpose of this paper is to provide an updated critical assessment of all available basic information for each genus, in order to obtain a sound database to study the generic paleodiversity of marine bivalves in the time interval from Induan (Early Triassic) to Sinemurian (Early Jurassic). This was a critical time for bivalve evolution and diversification, which began with the recovery from the Permian-Triassic extinction and ended with the recovery from the Triassic-Jurassic extinction.